2007
DOI: 10.1107/s1600536806053335
|View full text |Cite
|
Sign up to set email alerts
|

10,11-Dihydrocarbamazepine (form III)

Abstract: Key indicatorsSingle-crystal X-ray study T = 150 K Mean (C-C) = 0.003 Å R factor = 0.041 wR factor = 0.101 Data-to-parameter ratio = 12.6For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 7 publications
(6 reference statements)
0
18
0
Order By: Relevance
“…This is thought to allow for the optimization of the hydrogen bonding in a chain motif 13. All three structures of dihydrocarbamazepine also exhibit an analogous hydrogen bonding scheme to OCB, as they all form hydrogen bonded chains 7–9. The hydrogen bonding in all four of the carbamazepine polymorphs favor an anti‐dimer motif,6 whereas the structure of epoxycarbamazepine displays a twisted syn‐dimer configuration 18.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is thought to allow for the optimization of the hydrogen bonding in a chain motif 13. All three structures of dihydrocarbamazepine also exhibit an analogous hydrogen bonding scheme to OCB, as they all form hydrogen bonded chains 7–9. The hydrogen bonding in all four of the carbamazepine polymorphs favor an anti‐dimer motif,6 whereas the structure of epoxycarbamazepine displays a twisted syn‐dimer configuration 18.…”
Section: Resultsmentioning
confidence: 99%
“…Carbamazepine (CBZ) (Fig. 1), an important anticonvulsant, exhibits four structurally characterized polymorphs,6 whereas its dihydro derivative (10,11‐dihydrocarbamazepine) is trimorphic 7–9. Its keto‐derivative, oxcarbazepine (OCB) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The single‐crystal structure of sulfapyridine Form‐VI has been described, demonstrating that the asymmetric unit contains two different tautomeric forms that formed separate hydrogen‐bonded networks which interpenetrate 67. The crystal structures of new polymorphic forms of carvedilol,68 palonosetron hydrochloride,69 and 10,11‐dihydrocarbamazepine70 have been reported, and it has been shown that the crystal structure of methyl paraben obtained at a temperature of 118 K does not represent a new polymorph 71…”
Section: Structural Characterization and Properties Of Polymorphs Andmentioning
confidence: 99%
“…For details of experimental methods used to obtain this compound, see: Florence et al (2003); Florence, Johnston, Fernandes et al (2006). For related crystal structures, see: Bandoli et al (1992); Cyr et al (1987); Harrison et al (2006); Leech et al (2007); Fleischman et al (2003); Florence, Johnston, Price et al (2006); Florence, Leech et al (2006); Johnston et al (2006Johnston et al ( , 2007. For related literature, see: Etter (1990).…”
Section: Related Literaturementioning
confidence: 99%